MiR122-controlled all-in-one nanoplatform for in situ theranostic of drug-induced liver injury by visualization imaging guided on-demand drug release. (September 2021) - Meng, Lingchang; Wang, Qiaolei; Wang, Lai; Zhao, Zhen; Xin, Gui-Zhong; Zheng, Zuguo; Zhou, Ping; Li, Ping; Jiang, Yan; Li, Hui-Jun
Abstract: Drug-induced liver injury (DILI) is a challenging clinical problem with respect to both diagnosis and management. As a newly emerging biomarker of liver injury, miR122 shows great potential in early and sensitive in situ detection of DILI. Glycyrrhetinic acid (GA) possesses desirable therapeutic effect on DILI, but its certain dose-dependent side effects after long-term and/or high-dose administration limit its clinical application. In this study, in order to improve the precise diagnosis and effective treatment of DILI, GA loaded all-in-one theranostic nanoplatform was designed by assembling of upconversion nanoparticles and gold nanocages. As a proof of concept, we demonstrated the applicability of this single-wavelength laser-triggered theranostic nanoplatform for the spatiotemporally controllable in situ imaging of DILI and miR122-controlled on-demand drug release in vitro and in vivo . This novel nanoplatform opens a promising avenue for the clinical diagnosis and treatment of DILI. Graphical abstract: Image 1